To condemn is not to punish: An experiment on hypocrisy - Michael von Grundherr; Johanna Jauernig; Matthias Uhl (Games, 2021)
Hypocrisy is the act of claiming moral standards to which one's own behavior does not conform. Instances of hypocrisy, such as the supposedly green furnishing group IKEA's selling of furniture made from illegally felled wood, are frequently reported in the media. In a controlled and incentivized experiment, we investigate how observers rate different types of hypocritical behavior and if this judgment also translates into punishment. Results show that observers do, indeed, condemn hypocritical behavior strongly. The aversion to deceptive behavior is, in fact, so strong that even purely self-deceptive behavior is regarded as blameworthy. Observers who score high in the moral identity test have particularly strong reactions to acts of hypocrisy. The moral condemnation of hypocritical behavior, however, fails to produce a proportional amount of punishment. Punishment seems to be driven more by the violation of the norm of fair distribution than by moral pretense. From the viewpoint of positive retributivism, it is problematic if neither formal nor informal punishment follows moral condemnation.
Keywords: 330; 330; behavioral ethics; corporate hypocrisy; experimental ethics; moral identity; moral judgment; punishment